Labconcept Company’s New HPLC System LicArt 62 - article Editorial (Разработка и регистрация лекарственных средств)
Labconcept Ltd. company is the official distributor of the world`s leading analytical and laboratory equipment producing companies. In addition to that, Labconcept company has developed its own analytical equipment OEM-brand SILab. Various instruments under that trademark are already available on the Russian market: atomic absorption spectrophotometers, FTIR and UV-Vis spectrophotometers, TOC analyzers and ion-exchange liquid chromatography systems. LicArt 62 is a new product of Labconcept company. It is an HPLC system with modular design and with a wide range of detectors and several pump modifications available. Main blocks of LicArt 62 HPLC systems are assembled and tuned-up in Saint-Petersburg . After that all assembled instruments are thoroughly tested at the company`s Technical Control Department. Technical parameters of LicArt 62 HPLC systems perform technical parameters comparable or even superior to those of the world`s leading HPLC systems that are no longer available on the Russian market.